JUAL BELI TERPAKSA DALAM PERSPEKTIF HUKUM ISLAM - Ningsih Randiyah Nasution (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2024)
This paper discusses forced buying and selling, which in this paper the author tries to see forced buying and selling in the eyes of Islamic law. in this article the author uses a qualitative method that is looking for literature that discusses this issue including the books of fiqh muamalah. In a search conducted by the author, it was found that buying and selling with coercive elements in the concept of Islamic buying and selling is strictly prohibited. However, if buying and selling is not forced but due to being forced to sell at a low price in an emergency situation it is okay, but if the situation is conducive then the buyer is obliged to confirm the price of the items purchased during the emergency to be valued at the appropriate price. For more details, please refer to the full discussion in this article